2021
DOI: 10.1007/s11739-021-02842-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics and outcomes of patients admitted to hospital with COVID-19 during wave 1 and wave 2 of the current pandemic

Abstract: In this study of patients admitted with COVID-19, we examined differences between the two waves in patient characteristics and outcomes. Data were collected from the first COVID-19 admission to the end of study (01/03/2020–31/03/2021). Data were adjusted for age and sex and presented as odds ratios (OR) with 95% confidence intervals (CI). Among 12,471 admissions, 1452 (11.6%) patients were diagnosed with COVID-19. On admission, the mean (± SD) age of patients with other causes was 68.3 years (± 19.8) and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
12
1
1
Order By: Relevance
“…By contrast, COVID-19 admissions in wave-2 were more gradual, but the total number of admissions were much higher. We have demonstrated that non-COVID admissions mirrored closely the peaks and troughs of COVID-19 admissions [5].…”
Section: Patient Characteristicsmentioning
confidence: 64%
See 4 more Smart Citations
“…By contrast, COVID-19 admissions in wave-2 were more gradual, but the total number of admissions were much higher. We have demonstrated that non-COVID admissions mirrored closely the peaks and troughs of COVID-19 admissions [5].…”
Section: Patient Characteristicsmentioning
confidence: 64%
“…These findings were confirmed by multivariable logistic regression with adjustments for age, sex and CCI, showing no evidence for an increase in readmission or mortality amongst patients admitted during the pandemic compared to those admitted before the pandemic (reference group), within early, intermediate or late discharge group. These findings were corroborated by evidence that the numbers of patients admitted with general medical conditions was reduced with the surge of COVID-19 admissions with each pandemic wave [5]. However, there was no evidence for a decrease in the proportions of older adults or those with poorer health status (CCI) during either wave-1 or wave-2 of the COVID-19 pandemic.…”
Section: Patient Characteristicsmentioning
confidence: 88%
See 3 more Smart Citations